Webbed penis: A rare case - Agrawal, R; Chaurasia, D; Jain, M (Kathmandu University Medical Journal, 2010)
Webbed penis belongs to a rare and little-known defect of the external genitalia. The term denotes the penis of normal size for age hidden in the adjacent scrotal and pubic tissues. Though rare, it can be treated easily by surgery. A case of webbed penis is presented with brief review of literature. Key words: penis; webbed DOI: 10.3126/kumj.v8i1.3230 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 95-96